Scymicrosin7–26, a Scylla paramamosain-derived novel antimicrobial peptide, exhibits efficacy against multidrug-resistant ESKAPE pathogens and anti-inflammatory activity - Hu, Cong; Chen, Fangyi; Zhou, Ying; Yang, Ting; Wang, Kejian; Yang, Sheng; Chen, Xiangqi (Frontiers in Microbiology, 2025)
The escalating misuse of antibiotics has precipitated a worldwide crisis of bacterial resistance, greatly complicating the clinical management of multidrug-resistant bacterial infections, which now present a profound threat and a growing burden on public health systems. This situation necessitates the development of innovative anti-infective therapeutics. This work focuses on Scymicrosin7–26, a newly identified antimicrobial peptide (AMP) sourced from the crustacean Scylla paramamosain. AMPs typically derived from crustaceans are often characterized by suboptimal potency, instability, potential toxicity, and a narrow spectrum of activity, whereas Scymicrosin7–26 exhibits certain improvements in these regards. It exhibited antibacterial activity against five types of common clinically isolated multidrug-resistant organisms (MDROs). It inhibited both the formation and maturation of biofilms in carbapenem-resistant Pseudomonas aeruginosa (CR-PA) as well as methicillin-resistant Staphylococcus aureus (MRSA) without readily inducing resistance. Scymicrosin7–26 retained stable antimicrobial activity under physiological salt conditions and showed no significant antagonism when combined with several conventional antibiotics. It also demonstrated low toxicity toward RAW264.7, HEK293T, and Beas-2B cell lines, as well as human erythrocytes. Using fluorescence and electron microscopy, we observed disruption of bacterial surface structures. DNA binding assays further indicated the peptide’s capacity to interact with bacterial genomic DNA. Moreover, Scymicrosin7–26 alleviated lipopolysaccharide (LPS)-triggered inflammatory responses via concurrent blockade of MAPK and NF-κB pathway activation. With its antibacterial activity against multidrug-resistant pathogens, anti-inflammatory property, and safety profile, Scymicrosin7–26 exhibits therapeutic potential for managing infections caused by multidrug-resistant bacteria.